A Novel Forkhead Box Protein P (FoxP) From Litopenaeus vannamei Plays a Positive Role in Immune Response - Gao, Jiefeng; Geng, Ran; Deng, Hengwei; Zuo, Hongliang; Weng, Shaoping; He, Jianguo; Xu, Xiaopeng (Frontiers in Immunology, 2020)
The forkhead box protein P (FoxP) family members have been known to be important for regulation of immune responses in vertebrates, but their roles in invertebrate immunity remain unclear. In this study, a novel FoxP gene (LvFoxP) was identified from Pacific white shrimp Litopenaeus vannamei and functionally studied in the context of immune response. Possessing a conserved FoxP coiled-coil domain and a forkhead domain, LvFoxP shared homology to vertebrate FoxP family members, in particular FoxP1. Expression of LvFoxP was detectable in all the examined tissues and could be up-regulated by immune challenge in gill and hemocytes. The LvFoxP protein was present in both the cytoplasm and nucleus of hemocytes and could be nuclear-translocated upon immune stimulation. Silencing of LvFoxP increased the susceptibility of shrimp to infections by Vibrio parahaemolyticus and white spot syndrome virus (WSSV) and down-regulated the expression of multiple components of NF-κB and JAK-STAT pathways and almost all the examined immune effector genes. Moreover, the phagocytic activity of hemocytes from LvFoxP-silenced shrimp against V. parahaemolyticus was decreased. These suggested that LvFoxP could play a positive role in immune response. The current study may provide novel insights into the immunity of invertebrates and the functional evolution of the FoxP family.